Integration of Virtual Reality and Augmented Reality into STEAM Education: A Meta-Analysis - Khan Soomro, Raja Bahar; Basit Soomro, Abdul; Ali Shah, Syed Tassaduque; Memon, Ihsanullah (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2025)
Integration of Virtual Reality (VR) and Augmented Reality (AR) into the teaching of science, technology, engineering, arts, and mathematics (STEAM) has become so popular because of the impact on teaching and learning process. This meta-analysis explores the effects of VR and AR technologies in STEAM education based on a chain of studies undertaken over five years. The study analyses the impact of immersive technologies on student engagement, concept mastery, and skill development in various fields of science and technology. Research findings from various studies indicate that VR and AR support experiential learning by providing an immersive and interactive environment, which enables complex problem solving, creativity, and participation. In other words, VR provides a totally immersive experience that increases spatial consciousness and procedural abilities, but AR improves interaction with the physical environment and the real world. However, VR and AR effectiveness depends upon the level of education and the subject area and method of implementation. It is indicated that the results of the application of VR and AR show significant differences, as in most cases, VR offers deep experiences, whereas AR offers much opportunity to learn about the situation. The special emphasis of research is placed on intentional use of technology and strategies for education. It has identified some key areas that require further study to enhance the application of VR and AR technology in education and to have a higher impact on learning outcomes.